Landslide disaster risk perception in times of COVID-19: A student’s perspective - Karla María Hernández-Cadena; Irasema Alcántara-Ayala (Acta Universitatis Carolinae Geographica)
This study aimed to understand landslide risk perception among 15 to 20-year-old students in Teziutlán, Puebla, from 2018 to 2022 during the COVID-19 pandemic, a period in which communicating risks and providing information to the public were of utmost significance. The research involved a quantitative approach, using structured questionnaires to measure the level of risk perception within a specific population of young people residing in mountainous regions prone to landslides. A representative sample of 77 students from Antonio de Mendoza High School was interviewed using intentional sampling based on location and age. The study followed a comprehensive, multi-phase approach, which included developing indicators, obtaining informed consent, administering the questionnaire, ensuring voluntary participation, and data analysis. Young individuals interviewed showed a higher level of knowledge about the occurrence of landslides than what previous studies had reported. However, the global crisis resulting from the COVID-19 pandemic overshadowed the dissemination of information about landslides and other hazards.